The ovarian, ecdysterone, and heat-shock-responsive promoters of the Drosophila melanogaster hsp27 gene react very differently to perturbations of DNA sequence. - Hoffman, E P (1987)
The effect of various types of DNA sequence alterations on the activity of the ovarian, ecdysterone, and heat-shock-responsive promoters of the Drosophila melanogaster hsp27 gene was studied by P element-mediated germ line transformation. Regions of DNA required for proper expression of the gene under these different conditions were identified. Wild-type levels of transcription during oogenesis are dependent on two elements respectively located within a 64-base-pair (bp) fragment in the transcribed untranslated region and between -227 and -958 bp upstream of the transcription start site. This ovarian expression is particularly sensitive to both chromosomal position effects and an increased distance between the distal upstream promoter element and the TATAA homology. The ecdysterone-mediated expression during metamorphosis is dependent on a 145-bp domain including the TATAA box and additional upstream sequences that augment transcription by two- to five-fold. Finally, sequences necessary for heat shock expression are located much further upstream from hsp27 than those previously found for hsp70, although basal expression was correlated with the presence of more proximal heat shock consensus sequences.